THE PHENOMENA OF DERIVATION IN ENGLISH - Alimova Zarifa Vaxobovna (Western European Studies, 2024)
In this article, the process of derivation ensures the continuous improvement of the language, it is made using affixes, i.e., prefixes and suffixes, like in other languages, the characteristics of derivational formants in word formation in English and their functions in the sentence, prefixes are the main word It is said that 'z does not change the class, that is, a prefix is added to a noun to create a new noun with a different meaning, auxiliary suffixes can usually change both the meaning and the word group. Also, considerations are made on how to express the place of these formants in the use of language
Keywords: derivation; language; language development; addition